Usability Test of Web Tourism Applications to Increase the Attractiveness of Tourist Destinations in Magetan Regency, East Java: Uji Usabilitas Aplikasi Wisata Web untuk Peningkatan Daya Tarik Destinasi Wisata di Kabupaten Magetan, Jawa Timur - Priyono, Kuswaji Dwi; Nugroho, Danang (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Tourism destinations in Magetan Regency are one of the superior products in generating local revenue, but are not yet supported by pure, dynamic websig technology to increase the attractiveness of existing tourist destinations. This research aims to compile a database for tourism applications using a web-based Geographic Information System by analyzing the usability test results of tourist applications, so that they can become web-based tourism applications for the community. The method used in this research is the quantitative waterfall method to build a web-based tourism application. The database used in the Magetan Kumandang web-based tourism application uses 3 databases, namely PostGIS, Geoserver and phpMyAdmin. The Magetan Kumandang web-based tourism application interface was created using PHP programming supported by JS, HTLM, Leaflet and CSS. The results of the calculation of the usability test data for the Magetan Kumandang webgis tourism application produced a feasibility percentage value of 75.6% or included in the